1998
DOI: 10.1111/j.1440-1746.1998.tb00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis G virus in multitransfused thalassaemics from India

Abstract: Hepatitis G virus (HGV)/GB virus-C (GBV-C) has been identified as a blood-borne agent with disputed pathogenicity. This virus belongs to the flaviviridae with a distant relationship to hepatitis C virus (HCV). Genetically divergent HGV isolates have been reported from different parts of the world. This study describes the prevalence of HGV in multitransfused thalassaemic children in India and genomic sequence variations in 11 HGV isolates from the same geographical location. Hepatitis G virus RNA was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
0
1
Order By: Relevance
“…In this study, it was observed that all the Indian isolates of HGV clustered together on a distinct phylogenetic branch, suggesting that all isolates are genetically identical and showed maximum homology with the Chinese strain, in contrast with an earlier study from India which showed two strains with maximum homology with those from the USA [27]. This demonstrates that, because of high heterogeneity, strains from the same geographical area might belong to different lineages and show genetic relatedness to isolates from different parts of the world.…”
Section: Discussioncontrasting
confidence: 80%
“…In this study, it was observed that all the Indian isolates of HGV clustered together on a distinct phylogenetic branch, suggesting that all isolates are genetically identical and showed maximum homology with the Chinese strain, in contrast with an earlier study from India which showed two strains with maximum homology with those from the USA [27]. This demonstrates that, because of high heterogeneity, strains from the same geographical area might belong to different lineages and show genetic relatedness to isolates from different parts of the world.…”
Section: Discussioncontrasting
confidence: 80%
“…However, TTV and HGV infections were also recorded in as many as 24% and 4 % respectively of control subjects indicating involvement of non-parenteral routes of transmission (Schrotter et al, 2000;Okamoto et al, 1998). In the present study, prevalence of TTV and HGV co-infections with HCV infection among thalassemic subjects were found to be comparable to that reported in studies from India (Panigrahi, Saxena, Acharya & Panda, 1998;Asim, Potukuchi, Arora, Singh & Kar, 2008). Several studies based on liver enzyme profile concluded that neither HGV nor TTV has any pathogenic role in liver damage (Sampeitro et al,1997;Irshad, Joshi, Sharma & Dhar 2006;Matsumoto et al,1999).…”
Section: Discussionsupporting
confidence: 79%